Tafsir Furat KÙfi - Maryam Qubadi (حکمت اسرا)
One of the outstanding characteristics of contemporary research and study in the field of Islamic sciences is the re-examination of ancient texts from the first centuries. Some of the results deriving from such an approach and viewpoint are: the confirmation of the rootedness of the ShiÝi intellectual tradition; the recognition of existing deficiencies with a view towards alleviating them; and finally, the taking of decisive steps towards the enrichment and expansion of the breadth and depth of these studies in their various levels.One of these early works in the field of QurÞÁnic and traditional studies is an exegesis dating back to the third century and the beginning of the fourth century hijri entitled TafsÐr FurÁt KÙfÐ. This exegesis is mainly composed of traditions and narrations that are highly interpretative (tawili) and extensive (tatbiqwajary – where general principles derived from verses are applied and extended to referents beyond the strictly historical). It also contains a small number of traditions that are either esoteric, or that expound the historical context of verses as well as other unrelated historical accounts. Even though the compiler of the exegesis, FurÁt from KÙfah, Iraq, was not known and remains an unknown figure, based on the type of traditions that he has gathered in the book it can be said that he was a ZaydÐShiÝa with mystical inclinations. Like many other similar traditional books the TafsÐr FurÁt is not freeof fake and counterfeit traditions, but the number of such traditions is not large. So while the existence of a few problematic narrations cannot be overlooked, it in no manner depreciates from the authenticity and value of the many other traditions contained in the exegesis. Finally, the reason that this exegesis is relatively unknown is not so much due to the above mentioned weaknesses as it is to the fact that it contains narrations that are not meant for the general public and that are alluded to by the Immaculates (Ýa) as matters that should remain hidden—except from the adepts of the esoteric sciences.